Discrete modeling of nonlinear unvaried dynamic systems with first-order approach (2019)
This article shows a method to obtain a black box dynamic model of a nonlinear univariated system. A formal theoretical deduction is proposed to justify the procedure and steps to be followed are reported in order to implement them to any univariated system. Two examples are used to validate the explained methodology: a simulated nonlinear univariated system and a direct current motor separately excited. In both cases, the model obtained by difference equations is a segmented linearization of the algebraic function between both input and output variables. Parameters in that equation are dependent of input variable. The explained methodology can be included as an experimental practice in engineering subjects about control theory, modeling and simulation of dynamic systems.